Perlindungan Hukum bagi Nasabah Terhadap Risiko dalam Perjanjian Kredit Bank - Dewa Made Natha Dwitama; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2023)
Credit provided by banks contains risks so that in its implementation, banks must pay attention to the principles of sound credit. With this in mind, in providing credit, the bank is obliged to conduct an analysis of the debtor's ability to pay its obligations. In addition, banks are also required to review, assess and bind the collateral offered by the debtor, so that the collateral received can meet the requirements of applicable regulations. Banks in the activity of providing funds for credit must be based on a guarantee, which gives confidence to the bank on the debtor's ability to repay the credit in accordance with the agreement, and legal protection efforts for customers against risks in bank credit agreements, are pursued by means outside the court (Non litigation) through arbitration, which is carried out by making an arbitration agreement and through a general court (litigation).